Price dynamics in the eastern Caribbean - Sun, Yan (IMF [Washington]US, 2008)
Examines the influence of the pegging of the EC dollar to the US dollar on ECCU price stability. Analyzes whether absolute Purchasing Power Parity holds within the currency union. Shows that U.S. price stability has helped anchor price movement in the ECCU.